Rocky 4 - Stallone, Sylvester (Pasig City : Viva Video.)
East meets West Rocky takes on a vicious Soviet fighter who literally killed his last opponent! Sylvester Stallone writes, directs and stars in this war between nations in which the only battle is fought in a boxing ring. Rocky must defend his honor, his friend and America itself. Rocky proudly holds the heavyweight boxing championship, but a new challenger has stepped forward: Drago (Dolph Lundgren), a six-foot four-inch, 261-pound fighter who has the backing of the Soviet Union. Rocky's friend, Apollo Creed (Carl Weathers) fights Drago in an exhibition match, but after Creed's fatal defeat, Rocky knows he must avenge his friend and beat the Soviet adversary. Rocky's training regimen takes him to icy Siberia, where he prepares for a globally-televised match in the heart of Mascow. It's a powerfully-charged event as Rocky tales on Drago in a heart-pounding fight to the finish. Co starring Talia Shire, Burt young and Brigitte Nielsen, Rocky IV is a star-spangled tale of heroism and triumph Stallone once again packs a powerful punch, crafting a riveting film that pulsates with humor, searing drama and unabashed patriotism.